Botnet Prevention Strategies for Social Network Users: Cases and Remedies - Nishikant C Dhande (International Journal of Informatics and Communication Technology (IJ-ICT), 2013)
A Botnet is a collection of computers infected with malicious code that use FTP, TFTP, and HTTP protocol based services for infecting the computers. They keep on spreading till a desired strength of Botnet is assembled. Since social networking users have inclination to grow the Social Networks, a poorly designed social networking website can have some loop holes which could invoke a Botnet to spread around the users connected to it.  In this paper attempt is made to elaborate assimilation of social networks and to show how they can turn into Botnet. This study is based on the analysis of spam, Internet blogs, newsgroups & Cases for converging into conclusionsDOI: http://dx.doi.org/10.11591/ij-ict.v2i1.1819